UPAYA MENINGKATKAN HASIL BELAJAR LOMPAT JAUH GAYA MELENTING MENGGUNAKAN GAYA MENGAJAR INKLUSI - Tomy Priya Dinata; Waluyo Waluyo (PHEDHERAL, 2018)
The purpose of this study is To Improve Results Long Jump learning styles bouncy Students Grade XI IPA 3 SMA Negeri 1 Kartasura Academic Year 2017/2018.This research is a classroom action research are conducted in two cycles, with each cycle consisting of 2 meetings. The research subjects were the students grade XI 3 totaling 37 learners, Source of data derived from learners, teachers, and researchers. Data collection techniques are observation, interviews, documentation or archives are photographs. The validity of the data using data triangulation technique. Data were collected at each observation of the implementation cycle by qualitative descriptive analysis, using techniques percentage to view trends in learning activities.Based on the analysis in chapter IV obtained pre-cycle improvement occurring in the first cycle to and from the first cycle to the second cycle, In the long jump pre-cycle learning outcomes bouncy style on the criteria enough 27.02%, approximately 35.14%, and 37.84% less once the number of learners who pass are 10 learners. In the first cycle of learning outcomes long jump bouncy style in the good category of 13.51%, just 43.24%, 27.03% less, and less once 16.22%, the number of learners who completed 21 learners with a percentage of 56.76%. While on the second cycle of learning outcomes long jump bouncy style in the very good category for 5.41%, good 32.43%, 45.95% enough, lacking 13.51%, and less so 2.70%, The number of learners who complete and pass are 31 learners, of a total of 37 pesra students with a percentage of 83.78%. The increase occurred in the first cycle and the second cycle. Learning outcomes long jump bouncy style has reached the target to be achieved in the second cycle even exceeding the target.From the analysis of the above data it can be concluded thatusing a modification of inclusion style of teaching learning media can improve learning outcomes long jump on the bouncy style of learners in class XI IPA 3 SMA Negeri 1 Kartasura year 2017/2018 Teachings.